Efficacy and safety of mycophenolate mofetil in treating immune‐related hepatitis induced by immune checkpoint inhibitor use: A retrospective study. Issue 2 (13th February 2023) - Kadokawa, Yukio; Inoue, Satoko; Tatsumi, Akitoshi; Uchida, Mayako; Fujita, Keiko; Takagi, Mari; Inoue, Takako; Ohe, Shuichi; Nakai, Yasutomo; Otsuka, Tomoyuki; Abe, Yutaro; Nakabori, Tasuku; et al.
Abstract: Background and Aim: To investigate the outcomes in eight Japanese patients with cancer treated with mycophenolate mofetil (MMF) and corticosteroids for immune checkpoint inhibitor treatment‐induced severe immune‐related hepatitis (ir‐hepatitis) and the efficacy and safety of MMF. Methods: We retrospectively examined patient background, treatment course, as well as examination and imaging data using electronic medical records. Results: The ratio of male to female patients was 7:1, and the median age was 60 years (27–72 years). There were five and two cases of kidney cancer and malignant melanoma, respectively, and one case of lung cancer. The median number of days until MMF administration in addition to systemic corticosteroid therapy after the onset of ir‐hepatitis was 14.5 (2–42). The patients were categorized as four "good responders" who showed an improvement in the liver function tests following MMF treatment and four "poor responders" who did not. Furthermore, the time from the onset of ir‐hepatitis to initial MMF administration was significantly shorter in good responders (median 3 days, range 2–15 days) than in poor responders (median 25.5 days, range 14–42 days) ( P = 0.042). No significant intergroup difference was observed in other clinical factors. No serious adverse events caused by MMF were observed in any case. Conclusions: According to these findings, early recognition of corticosteroid refractoriness and the use of MMF may be beneficial in patients with ir‐hepatitis. Abstract : We investigated the efficacy and safety of mycophenolate mofetil (MMF) for eight Japanese patients with cancer treated with MMF and corticosteroids for immune checkpoint inhibitor treatment‐induced severe immune‐related hepatitis. The duration from the onset of immune‐related hepatitis (ir‐hepatitis) to initial MMF administration was significantly shorter in good responders than in poor responders ( P = 0.042). Early recognition of steroid refractoriness and the usage of MMF may be beneficial in patients with ir‐hepatitis.